2008
DOI: 10.1002/adfm.200700583
|View full text |Cite
|
Sign up to set email alerts
|

Uniformly Shaped Poly(p‐phenylenediamine) Microparticles: Shape‐controlled Synthesis and Their Potential Application for the Removal of Lead Ions from Water

Abstract: A novel method for the shape‐controlled synthesis of uniformly‐shaped poly(p‐phenylenediamine) (PpPD) microparticles with different morphologies under ambient condition has been developed using HAuCl4 as an oxidant and poly(N‐vinylpyrrolidone) (PVP) as a surfactant. The results demonstrate that the morphologies of these microparticles can be varied from symmetrical spindle‐like to diamond‐like, centrosymmetric leaf‐like, and parallelogram‐like by tuning the concentration of reactants and their molar ratios. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(61 citation statements)
references
References 41 publications
2
57
0
Order By: Relevance
“…This is also the same trend in the case of PoPD solid sub-microspheres. This phenomenon is also seen when poly(p-phenylenediamine) microparticles are used as adsorbent for Pb(II) ions [31]. However, the underlying mechanisms are not well-understood so far.…”
Section: Structural Characterizations Of Popd Hollow and Solid Submicmentioning
confidence: 96%
See 2 more Smart Citations
“…This is also the same trend in the case of PoPD solid sub-microspheres. This phenomenon is also seen when poly(p-phenylenediamine) microparticles are used as adsorbent for Pb(II) ions [31]. However, the underlying mechanisms are not well-understood so far.…”
Section: Structural Characterizations Of Popd Hollow and Solid Submicmentioning
confidence: 96%
“…As for Pb(II) ions adsorption capacity, it is seen to decrease with increasing adsorbent dosage. What's surprising is the adsorption capacity can reach as high as 4700 mg g À1 together with adsorptivity of 86.5% for PoPD hollow sub-microspheres and 3295 mg g À1 together with adsorptivity of 58.0% for PoPD solid sub-microspheres, which are much higher values than those of other materials [16,17,[28][29][30][31]34,35].…”
Section: Structural Characterizations Of Popd Hollow and Solid Submicmentioning
confidence: 98%
See 1 more Smart Citation
“…PPDA with microstructure, for example, nanorods, nanospheres, leaf-like, petal-like, diamond-like microparticles, multi-angula microrods, or dendalion-like microparticles, have been reported. In these, pH, oxidizing agent concentration, oxidizing agent to monomer molar ratio, or surface additives (surfactants or water-soluble polymers) were the shape driving conditions [5,11,24,47,48]. This indicates that diverse variables determine microstructure, most of them not related with the monomer itself.…”
Section: Morphologymentioning
confidence: 96%
“…They found that Electronic supplementary material The online version of this article (doi:10.1007/s00396-015-3667-8) contains supplementary material, which is available to authorized users. the presence of PVP is an important condition in microstructure control (spindle-like, diamond-like, centrosymmetric leaf-like, and parallelogram-like) [11]. The group of Sun et al synthesized core-shell composites using silver nanoparticles as the shell.…”
Section: Introductionmentioning
confidence: 99%